Chromosome Conformation Capture Carbon Copy (5C): A massively parallel solution for mapping interactions between genomic elements - Dostie, Josée (Cold Spring Harbor Laboratory Press, 2006)
Physical interactions between genetic elements located throughout the genome play important roles in gene regulation and can be identified with the Chromosome Conformation Capture (3C) methodology. 3C converts physical chromatin interactions into specific ligation products, which are quantified individually by PCR. Here we present a high-throughput 3C approach, 3C-Carbon Copy (5C), that employs microarrays or quantitative DNA sequencing using 454-technology as detection methods. We applied 5C to analyze a 400-kb region containing the human β-globin locus and a 100-kb conserved gene desert region. We validated 5C by detection of several previously identified looping interactions in the β-globin locus. We also identified a new looping interaction in K562 cells between the β-globin Locus Control Region and the γ–β-globin intergenic region. Interestingly, this region has been implicated in the control of developmental globin gene switching. 5C should be widely applicable for large-scale mapping of cis- and trans- interaction networks of genomic elements and for the study of higher-order chromosome structure.